Superfuel : thorium, the green energy source for the future - Martin, Richard, 1958-. (New York : Palgrave Macmillan, 2012)
"In this groundbreaking account of an energy revolution in the making, award-winning science writer Richard Martin introduces us to thorium, a radioactive element and alternative nuclear fuel that is far safer, cleaner, and more abundant than uranium. At the dawn of the Atomic Age, thorium and uranium seemed to be in close competition as the fuel of the future. Uranium, with its ability to undergo fission and produce explosive material for atomic weapons, won out over its more pacific sister element, relegating thorium to the dustbin of science. Now, as we grapple with the perils of nuclear energy and rogue atomic weapons and mankind confronts the specter of global climate change, thorium is reemerging as the overlooked energy source that can wean us off our fossil-fuel addiction and avert the risk of nuclear meltdown"--
Includes index.
Keywords: Thorium; Thorium -- Separation; Nuclear fuels; Nuclear reactors -- Design and construction; Nuclear fuels -- United States -- History; Nuclear reactors -- United States -- Design and construction -- History; Energy; Green Fuel; Thorium. -- Energy Sources